THE HR SCORECARD PERSPEKTIF DALAM PENGUKURAN KINERJA PERUSAHAAN - RR. NIKEN PURBASARI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
Understanding the perspective of innovation, learning and growth of the Balanced Scorecard (BSC) as a performance measurement system, will help the company to innovate and continuous improvement with emphasis on Human Resources (HR) as an important investment to reach and improve the performance of the company in accordance with expected. Developing Human Resources (HR) scorecard can help companies to manage employee performance and aligned all employee swith key objectives, by assigning financial and non-financial companies goals, and can help assess the performance, control and take necessary corrective actions to achieve better corporate performance.